Análise de difusividade térmica em aço duplex UNS S32304 submetido a diferentes processos de soldagem TIG e tratamento térmico - Bolsanello, Marilia Fernandes (2016)
Thermal diffusivity of UNS S32304 stainless steel was evaluated with the purpose ofaggregate knowledge to the development of the radioactive material transportation containment receptacles project.The Flash Lased Method was used, which is based on unidimensional thermal diffusivity equation analytical solution. A carbon dioxide laser with Gaussian profile was used, with 10−6wavelength, 10√22⁄intensity and 10√22⁄diameter.A sample of material was analyzed as received, in order toobtain a reference diffusivity value, and to compare with the value provided by the supplier, which ensured the method effectiveness. Thereafter, a sample welded by TIG autogenous process, with argon shield gas, was tested to analyze the welding process influence under thermal diffusivity. A sample welded by the same procedure, but heat treated under 600 °C for 8 hours and cooled by air was also analyzed, to evaluate the effect of these steels exposure to high temperatures after welding. To do so, in both welded samples, points with variable distance to sample middle were taken, including molted zone, heat affected zone and base metal. Finally, obtained results were compared to previous optical microscopy, ray X diffraction characterization, micro hardness and residual stresses analysis. It could be observed that thermal diffusivity was affected not only by welding process but also by heat treatment. Most of the points presented reduced thermal diffusivity, assigned to a material thermal conductive reduction, harmful for the use in question, once it will respond slowly to thermal changes. The heat treated sample presented diffusivity values closer to the material as received, qualitative similar results were also observed on residual stresses tests, where thermal treatment equalized materials stress state. Besides that, the molting zone point, at the sample only welded, presented a thermal diffusivity value above the one founded at base metal, which can be related to structural changes caused by heating. Nevertheless, those are partial conclusions, reinforcing the need of deeper studies concerning stainless steel UNS S32304 thermal diffusivity.